Age and psychosocial contributors to well-being among older adults living with chronic pain - Amara Kohlert; Natasha L. Gallant; Taylor G. Hill (Cogent Psychology)
Objectives This study examined the influence of age variables along with psychosocial variables on well-being among older adults living with chronic pain.Methods Using a cross-sectional survey design, older adults living with chronic pain in Canada (N = 220) completed an online survey assessing age variables (ie age at onset of chronic pain, current age), psychosocial variables (ie pain catastrophizing, pain disability, physical functioning, psychological inflexibility), and well-being variables (ie autonomy, environmental mastery, self-acceptance, overall eudaimonic well-being).Results Current age, but not age of onset of chronic pain, significantly predicted eudaimonic well-being and self-acceptance. Physical functioning, pain catastrophizing, and pain disability significantly predicted eudaimonic well-being, autonomy, and environmental mastery. Pain catastrophizing also significantly predicted self-acceptance. With regards to the relative importance of effect sizes, physical functioning followed by pain catastrophizing were the most important factors contributing to autonomy, environmental mastery, and self-acceptance. These psychosocial factors were more important for self-acceptance than they were for autonomy or environmental mastery.Conclusion When living with chronic pain, the psychosocial variables of most importance to older adults’ well-being may be physical functioning and pain catastrophizing, and the development of psychological interventions for older chronic pain populations should account for these psychosocial factors.